1984
DOI: 10.1152/jn.1984.51.3.516
|View full text |Cite
|
Sign up to set email alerts
|

Projections of hindlimb dorsal roots to lumbosacral spinal cord of cat

Abstract: Single dorsal roots of spinal nerves that contribute to the cat lumbosacral plexus (L3-S2) were cut to evoke degeneration of centrally projecting axons. Serial sections throughout lumbosacral cord levels were impregnated by the Fink-Heimer method (20) to permit charting of the distribution patterns of segmental dorsal root afferent fibers. Afferent fibers that enter a single dorsal root have an extensive distribution to multiple cord segments; their longitudinal extent varies with entry level and with laminar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
0

Year Published

1985
1985
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 0 publications
2
7
0
Order By: Relevance
“…However, recent anatomical studies using specific markers of populations of fine-diameter primary afferent fibres have reported that some long-projecting fine-diameter primary afferent fibres were observed in Lissauer's tract and superficial layers of the dorsal horn (Traub er al., 1989;Sugiura er al., 1989;Traub et al, 1990), confirming previous results of Culberson and Brown (1984) in Lissauer's tract. Thus, in the present study, it is probable that the residual percentage of opioid binding observed beyond two segments could be related to the long-projecting fine-diameter primary afferent fibres.…”
Section: Fig 4 Autoradiographic Images Showing the Distribution Of supporting
confidence: 89%
“…However, recent anatomical studies using specific markers of populations of fine-diameter primary afferent fibres have reported that some long-projecting fine-diameter primary afferent fibres were observed in Lissauer's tract and superficial layers of the dorsal horn (Traub er al., 1989;Sugiura er al., 1989;Traub et al, 1990), confirming previous results of Culberson and Brown (1984) in Lissauer's tract. Thus, in the present study, it is probable that the residual percentage of opioid binding observed beyond two segments could be related to the long-projecting fine-diameter primary afferent fibres.…”
Section: Fig 4 Autoradiographic Images Showing the Distribution Of supporting
confidence: 89%
“…The superficial laminae of the spinal cord receive heavy and direct input from the thin primary afferents A␦ and C fibers and contain primarily nociceptive neurons some of which being identified as projecting to the thalamus (Besson and Chaouch 1987;Brown and Culberson 1981;Cervero and Connell 1984;Culberson and Brown 1984;Fitzgerald 1984;Light and Perl 1979;Mizumura et al 1993;Sugiura et al 1986Sugiura et al , 1988Sugiura et al , 1989Sugiura et al , 1993Fitzgerald 1983, 1986). More recently, several studies also have demonstrated that a high number of nociceptive neurons in the superficial laminae project to the PB area (Hylden et al 1985(Hylden et al , 1986aLight et al 1987Light et al , 1993; see also McMahon and Wall 1983).…”
Section: Introductionmentioning
confidence: 99%
“…On the thorax, dermatomes are arranged as a series of simple, partially overlapping bands, but on limb‐bearing regions of the body they are more complex in shape (Sherrington, 1893; Kuhn, 1953; Hekmatpanah, 1961; Fletcher & Kitchell, 1966; Pubols & Pubols, 1969; Kow & Pfaff, 1975; Brown & Koerber, 1978; Bailey et al ., 1984). Within the spinal dorsal horn, the organization of primary afferent terminals mirrors their organization in the periphery; afferents from neighbouring dermatomes are largely overlapping, while those from nonadjacent dermatomes are not (Culberson & Brown, 1984; Rivero‐Melián & Grant, 1991; Mirnics & Koerber, 1995a, b). Dermatomal organization and the degree of overlap between adjacent segments is consistent across many different organisms (reviewed in Scott, 1982), suggesting a common mechanism for their formation.…”
Section: Introductionmentioning
confidence: 99%